2018
DOI: 10.1038/s41598-018-21703-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of peri-operative hidden blood loss of elderly patients with intertrochanteric fractures treated by unreamed proximal femoral nail anti-rotation

Abstract: The purpose of this study was to quantify the peri-operative blood loss of elderly patients with intertrochanteric fractures treated by unreamed proximal femoral nail anti-rotation (PFNA) and analyze whether the substantial hidden blood loss was induced by initial trauma or the operation. The clinical data of 123 patients with intertrochanteric fracture treated with unreamed PFNA from Jan 2013 to Apr 2017 were analyzed retrospectively. Blood routine on admission day (ADM), pre-operative day one (PRE), post-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Hip fractures can result in obvious blood loss; more specifically, patients with ITFs may have an underestimated blood loss, which increases postsurgical morbidity [5][6][7]. However, initial hematocrit (Hct) or hemoglobin (Hb) screening may seem normal on admission of these patients to the emergency department [5][6][7]. The accurate estimation of hidden blood loss may predict the Hb drop after fracture fixation, which could potentially improve the overall survival of patients with ITF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures can result in obvious blood loss; more specifically, patients with ITFs may have an underestimated blood loss, which increases postsurgical morbidity [5][6][7]. However, initial hematocrit (Hct) or hemoglobin (Hb) screening may seem normal on admission of these patients to the emergency department [5][6][7]. The accurate estimation of hidden blood loss may predict the Hb drop after fracture fixation, which could potentially improve the overall survival of patients with ITF.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors that may have an impact on hidden blood loss, such as age, presence of an unstable fracture, intramedullary fixation, and general anesthesia, have been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A few literatures showed that the postoperative hidden blood loss is more than intra-operative blood loss. [45][46][47] Unfortunately, this presented meta-analysis didn't analyze the hidden blood loss. Therefore, only analyzing intraoperative blood loss may be unfair for the AR group.…”
Section: Operative Time Blood Loss and Transfusionmentioning
confidence: 99%
“…Hip fractures can result in obvious blood loss; more specifically, patients with ITFs may have an underestimated blood loss, which increases postsurgical morbidity (4)(5)(6). Initial hematocrit or hemoglobin screening may be normal when these patients are admitted to the emergency department (4)(5)(6). The accurate estimation of hidden blood loss may predict the hemoglobin drop after fracture fixation, which could potentially improve the overall survival of patients with ITF.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors that may have an impact on hidden blood loss, such as age, presence of an unstable fracture, intramedullary fixation, and general anesthesia, have been reported (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%